2007
DOI: 10.1002/pi.2307
|View full text |Cite
|
Sign up to set email alerts
|

Controlled free radical photopolymerization of styrene initiated by trithiocarbonate

Abstract: Density functional theory calculations are reported for prediction of the trends in CS bond dissociation energies and atomic spin densities for radicals using S,S′‐bis(α,α′‐dimethyl‐α‐acetic acid) trithiocarbonate (TTCA) and bis(2‐oxo‐2‐phenylethyl) trithiocarbonate (TTCB) as reversible addition fragmentation chain transfer (RAFT) reagents. The calculations predict that the value of the CS bond length (1.865 Å) of TTCA is longer than that (1.826 Å) of TTCB, and TTCA is more effective for the polymerization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…108 [275] St [71,275] (St-b-BA) [275] S S S 109 [284] S S S 110* [283] BA [70] tBA [283] AM [285] St [70,286] St-b-NIPAM [286] tBA [284] St [284] tBA-b-St [284] St-b-BA [284] St/AA [287] St/AA-b-St [287] St/MAH/NVP [288,289] (Continued) [290] 111b RЈ ϭ C 2 H 5 [290] 111c RЈ ϭ i C 3 H 7 [290] 111d RЈ ϭ t C 4 H 9 [290] 111e RЈ ϭ CH 2 Ph [290] 112 [290] S…”
Section: *unclassified
See 3 more Smart Citations
“…108 [275] St [71,275] (St-b-BA) [275] S S S 109 [284] S S S 110* [283] BA [70] tBA [283] AM [285] St [70,286] St-b-NIPAM [286] tBA [284] St [284] tBA-b-St [284] St-b-BA [284] St/AA [287] St/AA-b-St [287] St/MAH/NVP [288,289] (Continued) [290] 111b RЈ ϭ C 2 H 5 [290] 111c RЈ ϭ i C 3 H 7 [290] 111d RЈ ϭ t C 4 H 9 [290] 111e RЈ ϭ CH 2 Ph [290] 112 [290] S…”
Section: *unclassified
“…Recently, several groups have reported that the polymerization of monomers with primary amine functionality (273)(274)(275)(276) (Table 16) can be effectively controlled with the monomer as the ammonium salt and with no or minimal loss of the RAFT end-group. [90,152,153,166] Some of the more exotic monomer subjected to RAFT polymerization are included in the tables that follow.…”
Section: Raft Polymer Synthesesmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] A thiocarbonylthio compound, known as a classical RAFT agent, is a photosensitive molecule that readily undergoes reversible b-cleavage at the carbon sulfur bond and thus yields some control over the radical polymerization process under UV irradiation. [16][17][18][19][20][21] Some studies have also focused on UV-induced ATRP and the effect of UV-Vis radiation on the controlled nature of the polymerization process. [22][23][24][25][26][27] Although some success was achieved by the above techniques, the conditions for true photoinduced controlled radical polymerization were not attained.…”
Section: Introductionmentioning
confidence: 99%